Pengaruh Kepemilikan Pemerintah, Kepemilikan Institusional, dan Kepemilikan Manajerial terhadap Penyajian Kembali - Amelia Helsa; Evelyn Jovita; Sany Sany (Business Accounting Review, 2021)
Restatement is a matter that needs to be considered where the number of restatementscontinues to be known by the public. The results found from previous studies regarding the types ofownership have not shown consistent results so that this study aims to analyze the effect of types ofownership on restatement. In this study, restatement was measured by a dummy variable. Meanwhile,the independent variables used are ownership types. In addition, firm size and leverage are used ascontrol variables. The data used in this study is data originating from the financial sector listed on theIDX with purposive sampling technique in 2015-2020. The method uses logistic regression analysiswith Software Statistical Package For Social Science (SPSS). Based on the results of the study, itshows that government ownership and managerial ownership h